Magnetostratigraphic Chronology of a Cenozoic Sequence From DSDP Site 274, Ross Sea, Antarctica - Jovane, Luigi; Florindo, Fabio; Wilson, Gary; de Almeida Pecchiai Saldanha Leone, Stephanie; Hassan, Muhammad Bin; Rodelli, Daniel; Cortese, Giuseppe (Frontiers in Earth Science, 2020)
New paleomagnetic results from the late Eocene-Middle Miocene samples from Deep Sea Drilling Project Hole 274, cored during Leg 28 on the continental rise off Victoria Land, Ross Sea, provide a chronostratigraphic framework for an existing paleoclimate archive during a key period of Antarctic climate and ice sheet evolution. Based on this new age model, the cored late Eocene-Middle Miocene sequence covers an interval of almost 20 Myr (from ~35 to ~15 Ma). Biostratigraphic constraints allow a number of possible correlations with the Geomagnetic Polarity Time Scale. Regardless of correlation, average interval sediment accumulation rates above 260 mbsf are ~6 cm/kyr with the record punctuated by a number of unconformities. Below 260 mbsf (across the Eocene/Oligocene boundary) interval, sedimentation accumulation rates are closer to ~1 cm/kyr. A major unconformity identified at ~180 mbsf represents at least 9 Myr accounting for the late Oligocene and Early Miocene and may represent non-deposition and/or erosion due to intensification of Antarctic Circumpolar Current activity. Significant fluctuations in grain size and magnetic properties observed above the unconformity at 180 mbsf, in the Early Miocene portion of this sedimentary record, reflect cyclical behavior in glacial advance and retreat from the continent. Similar glacial cyclicity has already been identified in other Miocene sequences recovered in drill cores from the Antarctic margin.